Body roundness index and the risk of knee osteoarthritis: evidence from the China Health and Retirement Longitudinal Study - Zong Jiang; Xin Cai; Xin Cai; Xiaoling Yao; Weiya Lan; Xueming Yao; Fang Tang; Wukai Ma (Frontiers in Nutrition)
ObjectivePrevious cross-sectional studies have demonstrated that the body roundness index (BRI) is associated with knee osteoarthritis (KOA). However, no longitudinal studies have confirmed this association. This study aims to explore the link between BRI and KOA risk in the Chinese population through longitudinal analysis and to evaluate its utility in early diagnosis and risk prediction.MethodsThis study utilizes data from the China Health and Retirement Longitudinal Study (CHARLS). A total of 7,318 participants who were followed from 2015 to 2020 were included. BRI was calculated using physical examinations and questionnaire data, and participants were categorized by quartiles. The relationship between BRI and KOA risk was assessed using multivariate weighted regression models and trend tests, while subgroup and sensitivity analyses were conducted to ensure the robustness of the findings.ResultsAfter 5 years of follow-up, 1,035 participants (14.14%) were diagnosed with KOA. Findings indicate a positive correlation between BRI and KOA risk (HR = 1.08, 95% CI: 1.02–1.13, p = 0.0039), with an increasing trend in KOA risk across BRI quartiles (p for trend = 0.0033). Subgroup analysis reveals that the association is particularly strong among individuals aged 50–59, males, those living in rural areas, and those without cardiovascular disease.ConclusionThis study establishes that an increase in BRI significantly elevates KOA risk. These findings suggest that BRI could be an effective tool for KOA risk assessment and could contribute to the development of personalized prevention strategies. Additionally, BRI is valuable in elucidating the potential mechanisms linking body fat distribution and inflammatory responses in KOA progression.